2003
DOI: 10.1002/ajmg.a.20156
|View full text |Cite
|
Sign up to set email alerts
|

Under‐ascertainment of mosaic carriers of balanced homologous acrocentric translocations and isochromosomes

Abstract: Acrocentric rearrangements are the most common chromosome abnormalities in humans. Carriers of homologous acrocentric rearrangements (Robertsonian translocations (ROBs) between homologous chromosomes and isochromosomes) are at very high risk of having multiple spontaneous abortions and chromosomally abnormal offspring. Parents of fetuses and children with unbalanced homologous acrocentric rearrangements are rarely found to be carriers or mosaic for the same rearrangement. Even though recurrent miscarriages may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 63 publications
(40 reference statements)
4
18
0
Order By: Relevance
“…In a recent study, however, only one male was found among 10 carriers of mosaicism for homologous translocations or isochromosomes [Kovaleva and Shaffer, 2003]. There are not enough data on mosaic carriers of other types of structural anomalies because of the rarity of such cases.…”
Section: Introductionmentioning
confidence: 97%
“…In a recent study, however, only one male was found among 10 carriers of mosaicism for homologous translocations or isochromosomes [Kovaleva and Shaffer, 2003]. There are not enough data on mosaic carriers of other types of structural anomalies because of the rarity of such cases.…”
Section: Introductionmentioning
confidence: 97%
“…These second pool of normal spermatogonia would be in the origin of the 15.8 % normal sperm for chromosome 2 analyzed divisions after fertilization. As previously described [6], the presence of mosaicism for a normal cell line should be expected unless the rearrangement occur in the first zygotic cleavage where the chromatin is more unstable and more prone to rearrangements. In the present case, no normal cell line was found on lymphocytes and so, theoretically, no normal gametes and a successful pregnancy are expected.…”
Section: Discussionmentioning
confidence: 85%
“…In the present case, no normal cell line was found on lymphocytes and so, theoretically, no normal gametes and a successful pregnancy are expected. Even so, cryptic mosaicism is not possible to discard when analyzing only lymphocytes [6]. Mosaicism in other tissues is a hypothesis to be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations